Leadership Concept and Theories: Understanding Higher Education in Pakistan (Journal of Politics and International Studies, 2024)
The education sector plays a vital role in this study. This research paper studies two Higher Education Institutions (HEIs) of the Punjab University as a case study to comprehend the higher educational leadership in the HEIs. The impact of leadership on the IAS and IBA departments of the University of Punjab has been discussed. The Criteria of leadership have been used from the CAF model. Data has been collected through questionnaires, which lecturers and professors of both departments filled out. The scoring table has been used to compile the results. The study's findings show leadership's influential role in both the departments of the University of Punjab. The study also compares the departments by using the sub-criteria of leadership. It shows the working of the leaders in enhancing the performance of employees, in imparting mission, vision, and values, in acting as a role model, and also their role in developing relations with the stakeholders. The study results show that IBA performed better than the IAS department in fulfilling the above criteria. However, the study results are not generalizable since only two departments of the PU were considered for the research.